The relationship between diameter and taper of nickel-titanium rotary instruments on the torsional resistance to fracture - Erick Miranda Souza; Cláudia de Castro Rizzi Maia; Etevaldo Matos Maia Filho; Idomeo Bonetti Filho
Objective: To evaluate the resistance to fracture of rotary Ni-Ti files of various diameters and tapers after torsional stress simulation. Methods: Profile (Dentsply Maillerfer, Ballaigues, Suíça) instruments sizes 15 to 40, taper 0.04 and 0.06 were used. Ten instruments of each size and taper were tested, totaling 120 files. The maximum torque (Tmax) until fracture was determined in accordance with the ANSI / ADA Protocol Nº 28 . The maximum force was converted into maximum torque using the formula: Tmax = Loadmax x RadiusResults: The diameter (p<0.001) and taper (p<0.001) influenced the maximum torque to fracture. With the increase in diameter and taperthere was a gradual increase in the maximum torque. Using the multiple regression method an equation relating the maximum torque to the diameter (D) and the taper (T) was found: Tmax = -1.4 + 0.08D + 10.5T. Conclusion: The increase in diameter and taper promoted an increase in resistance to torsion. The variation of the taper from 0.04 to 0.06 in instruments with the same diameter increased resistance to fracture by torsion by around 25%.